Deranged iron status in psoriasis: the impact of low body mass. Issue 4 (15th November 2015) - Ponikowska, Malgorzata; Tupikowska, Malgorzata; Kasztura, Monika; Jankowska, Ewa A.; Szepietowski, Jacek C.
Abstract: Background: Iron deficiency (ID) frequently complicates inflammatory‐mediated chronic disorders, irrespective of anaemia. Psoriasis is a chronic, immune‐mediated skin disease with systemic pro‐inflammatory activation; thus, these patients may be prone to develop ID. ID adversely affects immune cells function, which can further contribute to disease progression. This study investigates iron status in psoriasis. Methods: Serum concentrations of ferritin, transferrin saturation (Tsat), soluble transferrin receptor (sTfR), and hepcidin were assessed as the biomarkers of iron status in 39 patients with psoriasis (17 men, age: 47 ± 10 years) and 44 healthy subjects (30 men, age: 53 ± 6 years). Results: Compared with healthy controls, patients with psoriasis demonstrated similar haematologic status but deranged iron status as evidenced by decreased Tsat and elevated sTfR (negative tissue iron balance) and low levels of hepcidin (depleted iron stores) (all P  < 0.05 vs. controls). In patients, the levels of interleukin‐6 (level of pro‐inflammatory activation) significantly correlated with hepcidin ( R  = 0.54), but not with ferritin, Tsat, and sTfR. Biomarkers reflecting ID were not associated with the severity of the disease (assessed with the Psoriasis Area and Severity Index) but significantly correlated low body mass index (BMI). Patients with BMI < 24 kg/m 2 compared with those with BMI ≥ 24 kg/m 2 demonstrated lower levels of ferritin (40 ± 30 vs. 186 ± 128 ng/mL, P  < 0.001) and hepcidin (4.9 ± 2.3 vs. 10.7 ± 6.7 ng/mL, P  = 0.03). Conclusion: Psoriasis is associated with deranged iron status characterized by depleted iron stores with concomitant unmet cellular iron requirements. The magnitude of these abnormalities is particularly strong in patients with low body mass index. Whether iron deficiency may become a therapeutic target in psoriasis needs to be investigated.